1982
DOI: 10.1113/jphysiol.1982.sp014199
|View full text |Cite
|
Sign up to set email alerts
|

Selective reinnervation of skeletal muscle in the newt Triturus cristatus.

Abstract: SUMMARY1. A study was made ofthe effectiveness ofsynapses formed by foreign and original nerves during reinnerv -,tion of skeletal muscle of the newt Triturus cri8tatu-8. The extensor cranialis nerve (e.c.n.) of the forelimb was implanted into the humeroantebrachialis muscle (biceps) which was denervated by cutting or crushing the forelimb flexor nerve (f.f.n.).2. Although biceps became innervated by the implanted nerve, neuromuscular transmission was abnormal. The ratio ofthe tensions developed by biceps dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

1984
1984
1996
1996

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
2
25
2
Order By: Relevance
“…Muscle fibres in axolotls possess synaptic sites which can distinguish between foreign and native segmental nerves throughout life (Cass & Mark, 1975;Bennett et al 1979;Holder, Mills & Tonge, 1982). The terminals of a foreign nerve have e.p.p.s with substantially lower quantal content than those of a native nerve (Holder et al 1982). Eventually the foreign nerves are eliminated from synaptic sites by the native nerves (Dennis & Yip, 1978;Bennett et al 1979).…”
Section: Selectivity Of Synaptic Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle fibres in axolotls possess synaptic sites which can distinguish between foreign and native segmental nerves throughout life (Cass & Mark, 1975;Bennett et al 1979;Holder, Mills & Tonge, 1982). The terminals of a foreign nerve have e.p.p.s with substantially lower quantal content than those of a native nerve (Holder et al 1982). Eventually the foreign nerves are eliminated from synaptic sites by the native nerves (Dennis & Yip, 1978;Bennett et al 1979).…”
Section: Selectivity Of Synaptic Sitesmentioning
confidence: 99%
“…Evidence that synaptic sites can favour one nerve over another comes from studies on amphibia. Muscle fibres in axolotls possess synaptic sites which can distinguish between foreign and native segmental nerves throughout life (Cass & Mark, 1975;Bennett et al 1979;Holder, Mills & Tonge, 1982). The terminals of a foreign nerve have e.p.p.s with substantially lower quantal content than those of a native nerve (Holder et al 1982).…”
Section: Selectivity Of Synaptic Sitesmentioning
confidence: 99%
“…In recent experiments on amphibia however, histological and electrophysiological evidence revealed that axons from the stump of a foreign nerve appeared to form synapses only at the denervated original end-plates, despite being implanted several millimetres from them (Holder, Mills & Tonge, 1982;Sayers & Tonge, 1982a). In contrast, ectopic synapse formation has been observed in the frog following nerve implantation into the end-plate-free region of a bisected sartorius muscle (Miledi, 1962(Miledi, , 1963Breitschmid & Brenner, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In amphibia, synapses formed by a foreign nerve are less effective than those formed by the regenerated original nerve (Holder, Mills & Tonge, 1982;Sayers & Tonge, 1982). In our initial experiments synapses formed by the h.n.…”
Section: Discussionmentioning
confidence: 99%